Building Ecological Awareness: Implementing Environmental Ethics and Sustainability in Indigenous Communities Through a Traditional Ecological Knowledge Approach - Taufik, Iqbal; Mustika, Amalia; Hidayat, Arif; Kogoya, Willius; Sutiapermana, Aden (PT Inovasi Pratama Internasional, 2024)
Efforts to preserve the environment and sustainability on the island of Bali, especially in the Tenganan, Penglipuran and Trunyan Traditional Villages, through a traditional ecological knowledge approach. This program aims to increase ecological awareness and implement environmental ethics and sustainability in indigenous communities. Implementation methods involve surveys, education, training, program implementation, and evaluation. The results show that through comprehensive education and training, as well as the implementation of sustainable programs, communities can adopt environmentally friendly practices and preserve their traditional ecological knowledge. Program impact evaluation re-engages indigenous communities to obtain feedback, ensuring the program is sustainable and effective. In conclusion, this program succeeded in combining various approaches to create positive changes in behavior and attitudes towards the environment in Balinese traditional communities, as well as strengthening their traditional ecological knowledge.